Adaptive repair device concept with shape memory polymer. (24th January 2017) - Zhao, Wei; Liu, Liwu; Lan, Xin; Su, Bo; Leng, Jinsong; Liu, Yanju
Abstract: Shape memory polymer (SMP) is a new kind of intelligent polymer, which can be activated by an external stimulus to change and subsequently recover its original shape. Due to this shape memory effect, SMP can be used in a wide range of engineering and biomedical applications. This paper details an application of SMP on manufacturing of a fracture fixation. The basic properties were characterized by dynamic mechanical analysis, and the stress relaxation and fatigue were established. An SMP-based fracture fixator was designed, analyzed, and optimized. Finally, the fixator was fabricated and the fixed effects were verified by experiment in vitro . The performance of the SMP-based fixator was excellent and proved to be a potential replacement for the traditional fracture fixator.